3 Can Redox-Sensitive Cysteines in P38A-MAPK Modulate Activation During Stress?. (19th January 2014) - Bassi, R; Rudyk, O; Burgoyne, J; Eaton, P; Marber, M S
Abstract : p38α-MAPK (p38α), a serine-threonine kinase plays a pivotal role in a variety of biological processes and is thus activated by diverse stimuli. Its activation is controlled by phosphorylation of two key residues, Thr180 and Tyr182 in the activation loop, by its archetypal upstream activator MKK3. This pathway responds to multiple stresses including oxidants. Our purpose was to determine if such activation is dependent on redox-sensing cysteines within p38α. Following the exposure of rat cardiomyocytes or whole hearts to H2 O2 (50 μM) p38α was activated and formed a heterodimer with MKK3 that was sensitive to reduction by mercaptoethanol. The abundance of this heterodimer was enhanced by co-administration of Auranofin (2 μM) suggesting redox cycling occurs in vivo . We predicted that either Cys119 or Cys162, both close to the known MKK3 docking domain, could act as electron donors and form a disulphide bridge with MKK3 (Cys29). Dimer formation was reduced by p38α Cys119Ser and increased by p38α Cys162Ser suggesting these residues act as vicinal thiols. p38α Cys119Ser/Cys162Ser was incapable of sensing H2 O2 . Interestingly, the formation of the heterodimer was also prevented, following exposure to the anti-inflammatory cyclopentanone 15-d PGJ2, a naturally occurring end product of prostaglandin D2 metabolism, that directly modifies the redox-sensitive thiols within p38α. The functional consequence of the p38α-MKK3 heterodimer is as yet unknown. However, our novel findings suggest it may act as a redox switch that plays a role in the dynamic regulation of p38α.